Survey Kepuasan Masyarakat Terhadap Pelayanan Di UPT Dinas Pendapatan Provinsi Riau - machasin, machasin; rifqi, achmad (Jurnal Daya Saing, 2015)
Abstract: This research was conducted aimed to measure the extent of public satisfaction with the services performed by the Riau Provincial Revenue Office with the policy of the Minister of State Apparatus No. 16 of 2014 on Public Satisfaction Survey guidelines for the implementation of the Public as necessary to build public confidence in the apparatus as publik services providers in order to improve the welfare of society. Samples of this study consisted of 17 UPT Riau Provincial Revenue Service with analytic descriptive analysis techniques. Results of this study result unit within the overall service of the Provincial Revenue Service is very good with service quality category A (Excellent) with a value of 89.76. Keywords: Satisfaction, Service, Riau, Apparatus, Public